DIAGNOSIS OF HEARING DAMAGE DUE TO NOISE IN INDUSTRIES: A REVIEW (World Bulletin of Public Health, 2023)
Noise-induced hearing loss (NIHL) is a prevalent occupational health issue affecting workers in various industries. The early diagnosis and management of hearing damage are crucial to prevent further deterioration and mitigate the impact on individuals' quality of life. This review article aims to provide an overview of the diagnostic methods utilized in identifying hearing damage caused by occupational noise exposure, with a focus on their relevance in industrial settings. We discuss the importance of early detection, the role of audiometric testing, and emerging technologies for improved diagnosis and monitoring of NIHL. Additionally, we explore the challenges and potential future directions in the field of diagnosing and managing hearing damage in industrial settings
Keywords: noise-induced hearing loss; NIHL